2004
DOI: 10.1140/epjb/e2004-00386-3
|View full text |Cite
|
Sign up to set email alerts
|

Scaling the $\alpha $ -relaxation time of supercooled fragile organic liquids

Abstract: :It was shown recently [1] that the structural α-relaxation time τ of supercooled o-terphenyl depends on a single control parameter Γ, which is the product of a function of density E(ρ), by the inverse temperature T -1 . We extend this finding to other fragile glassforming liquids using light-scattering data. Available experimental results do not allow to discriminate between several analytical forms of the function E(ρ), the scaling arising from the separation of density and temperature in Γ. We also propose … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
170
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(180 citation statements)
references
References 44 publications
(117 reference statements)
10
170
0
Order By: Relevance
“…Later, a similar scaling was found to work for other organic glass formers, including polymers, showing that the relaxation time is a function of h(ρ)/T [6][7][8]. There was some debate over the functional form of h(ρ) and whether it could be uniquely determined given the limited density changes experimentally available [9][10][11][12][13][14]. In a famous review Roland et al [15] demonstrated that scaling with h(ρ) = ρ γS with a material specific scaling exponent γ S works well for a large group of organic glass formers, including polymers.…”
Section: Introductionmentioning
confidence: 66%
“…Later, a similar scaling was found to work for other organic glass formers, including polymers, showing that the relaxation time is a function of h(ρ)/T [6][7][8]. There was some debate over the functional form of h(ρ) and whether it could be uniquely determined given the limited density changes experimentally available [9][10][11][12][13][14]. In a famous review Roland et al [15] demonstrated that scaling with h(ρ) = ρ γS with a material specific scaling exponent γ S works well for a large group of organic glass formers, including polymers.…”
Section: Introductionmentioning
confidence: 66%
“…On the basis of the existing data, it is reasonably well established that the temperature and density dependences of the alpha-relaxation time can be expressed in a scaling form as [10,11,12,13,14,15,16].…”
Section: Isochoric and Isobaric Fragilitiesmentioning
confidence: 99%
“…A remarkable development in understanding the relaxation and the transport of liquids and polymer melts was the discovery that the temperature (T ) and the density (ρ) dependence of, e.g., the structural relaxation time τ α and the viscosity η, can be scaled to a materialdependent master curve [3][4][5][6][7][8][9]: log τ α , log η = F T S (T ρ −γts )…”
Section: Introductionmentioning
confidence: 99%